Mesenchymal stem cells alleviate oxidative stress-induced mitochondrial dysfunction in the airways. - Li,X; Michaeloudes,C; Zhang,Y; Wiegman,CH; Adcock,IM; Lian,Q; Mak,JCW; Bhavsar,PK; Chung,KF (Journal of Allergy and Clinical Immunology, 2017)
BACKGROUND: Oxidative stress-induced mitochondrial dysfunction may contribute to inflammation and remodeling in chronic obstructive pulmonary disease (COPD). Mesenchymal stem cells (MSCs) protect against lung damage in animal models of COPD. It is unknown whether these effects occur through attenuating mitochondrial dysfunction in airway cells. OBJECTIVE: To examine the effect of induced-pluripotent stem cell-derived MSCs (iPSC-MSCs) on oxidative stress-induce mitochondrial dysfunction in human airway smooth muscle cells (ASMCs) in vitro and in mouse lungs in vivo. METHODS: ASMCs were co-cultured with iPSC-MSCs in the presence of cigarette smoke medium (CSM), and mitochondrial reactive oxygen species (ROS), mitochondrial membrane potential (ΔΨm) and apoptosis were measured. Conditioned media from iPSC-MSCs and trans-well co-cultures were used to detect any paracrine effects. The effect of systemic injection of iPSC-MSCs on airway inflammation and hyper-responsiveness in ozone-exposed mice was also investigated. RESULTS: Co-culture of iPSC-MSCs with ASMCs attenuated CSM-induced mitochondrial ROS, apoptosis and ΔΨm loss in ASMCs. iPSC-MSC-conditioned media or trans-well co-cultures with iPSC-MSCs reduced CSM-induced mitochondrial ROS but not ΔΨm or apoptosis in ASMCs. Mitochondrial transfer from iPSC-MSCs to ASMCs was observed after direct co-culture and was enhanced by CSM. iPSC-MSCs attenuated ozone-induced mitochondrial dysfunction, airway hyper-responsiveness and inflammation in mouse lungs. CONCLUSION: iPSC-MSCs offered protection against oxidative stress-induced mitochondrial dysfunction in human ASMCs and in mouse lungs, whilst reducing airway inflammation and hyper-responsiveness. These effects are, at least partly, dependent on cell-cell contact that allows for mitochondrial transfer, and paracrine regulation. Therefore, iPSC-MSCs show promise as a therapy for oxidative stress-dependent lung diseases such as COPD.